El costado occidental de la Plaza de Bolívar de la colonia al edificio Liévano - Delgadillo Suárez, Hugo Alberto (Pontificia Universidad Javeriana, 2014)
The following article studies the history of the structures that make up the western segment of the Plaza de Bolívar in the city of Bogotá. The origin of the Municipal Palace and the Lievano Building, which today house the Alcaldia Mayor de Bogotá, result from physical, political, economic and functional changes that took place between 1902-1906. This segment of the Plaza, given its history and architectural value, has been declared a National Monument.